2009
DOI: 10.1016/j.envpol.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The growth response of Alternanthera philoxeroides in a simulated post-combustion emission with ultrahigh [CO2] and acidic pollutants

Abstract: Although post-combustion emissions from power plants are a major source of air pollution, they contain excess CO2 that could be used to fertilize commercial greenhouses and stimulate plant growth. We addressed the combined effects of ultrahigh [CO2] and acidic pollutants in flue gas on the growth of Alternanthera philoxeroides. When acidic pollutants were excluded, the biomass yield of A. philoxeroides saturated near 2000 micromol mol(-1) [CO2] with doubled biomass accumulation relative to the ambient control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Alternanthera philoxeroides and P. canescens had high N concentrations (> 50 mg N g −1 ) in leaf tissue (Fig. 2c,d), as regularly observed in these two species cultured under glasshouse condition with adequate nutrient supply (Xu et al. 2009; C.‐Y.…”
Section: Resultssupporting
confidence: 74%
“…Alternanthera philoxeroides and P. canescens had high N concentrations (> 50 mg N g −1 ) in leaf tissue (Fig. 2c,d), as regularly observed in these two species cultured under glasshouse condition with adequate nutrient supply (Xu et al. 2009; C.‐Y.…”
Section: Resultssupporting
confidence: 74%
“…In a more recent study conducted on alligator weed ( Alternanthera philoxeroides ) it was shown that exposing plants to NO 2 (0.8–3.1 ppm) and SO 2 (0.09–0.35 ppm) emission scenarios designed to represent post‐combustion flue gases, alongside concurrent ultrahigh CO 2 concentrations (2000–5000 ppm), could partially compensate for the negative effects of the acidic pollutants and result in increased absorbance of excess CO 2 and higher yields (Xu et al . ). Taken together, these examples underline the major challenges in developing a full understanding of plant defence mechanisms in the natural environment.…”
Section: Plant Physiological and Molecular Responses To Combinations mentioning
confidence: 99%